Chromatin dynamics during plant sexual reproduction - She, Wenjing; Baroux, Célia (Frontiers in Plant Science, 2014)
Plants have the remarkable ability to establish new cell fates throughout their life cycle, by contrast to most animals that define all cell lineages during embryogenesis. This ability is exemplified during sexual reproduction in flowering plants where novel cell types are generated in floral tissues of the adult plant during sporogenesis, gametogenesis, and embryogenesis. While the molecular and genetic basis of cell specification during sexual reproduction is being studied for a long time, recent works disclosed an unsuspected role of global chromatin organization and its dynamics. In this review we describe the events of chromatin dynamics during the different phases of sexual reproduction and discuss their possible significance particularly in cell fate establishment.